بيئة المدرسة الداخلية والخارجية وعلاقتهما بالانخراط السلوكي والتحصيل الدراسي بمدارس محافظة شمال الباطنة في سلطنة عمان - خليل بن إبراهيم بن حسن البلوشي
This study aimed to investigate the internal and external school environment and their relationship to behavioral engagement and academic achievement in schools in Al Batinah North Governorate in the Sultanate of Oman. The study included some sub-aims: to explore the impact of the internal and external environment on the behavior engagement in its three sub-categories (Educational, schooling and perseverance), to investigate the possible relation between the internal and external environment and academic achievement, and to explore the possible differences between the internal and external environment on the behavior engagement attributed to the gender and the age. The researcher used the descriptive analysis method which suits the objectives of this study. The current study population consisted of 8580 students from secondary schools in the governorate distributed over the six states of North Al Batinah (Al-Suwaiq, Al-Khaboura, Saham, Sohar, Liwa, Shinas) which is the second largest governorate after Muscat with a ( 780899 ) population. By using Sample Cluster strategy 437 students were selected to be the sample of this study. The study used a quantitative approach. It used the internal school environment scale, the external school environment scale, and the behavioral engagement scale as tools of the study. The validity and reliability of the study tools were also verified, and it was valid and reliable for the scientific use. The researcher used a set of statistical methods to answer the research questions like exploratory factor analysis (EFA), multiple linear regression and multivariate analysis of variance (MANOVA). The results of the study showed that the study tool has psychometric properties that contribute to build the hidden root of the scales and the presence of statistical significance between the internal and external school environment and between learning engagement and achievement in the schools of Al Batinah North Governorate in the Sultanate of Oman. Also, the internal school environment had an effective role on school’s engagement. And there is no relationship between the external school environment and school engagement. On the other hand, the study showed that the external school environment had the greatest role on academic achievement. Moreover, the internal school environment has an inverse relationship in improving academic achievement. The results showed that there was a statistical significance between the internal school environment due to the gender goes to male category. While the academic achievement variable goes to the female category. On the other hand, there were no statistical differences between the external school environment, learning engagement, school achievement, and studying engagement due to the gender variable. The study recommended to facilitate the procedures which motivate students to engage them in the behavioral and academic achievement in the internal school environment and the external school environment according to the future vision of education in the sultanate of Oman.